Philosophy of the Information Society. Proceedings of the 30th International Ludwig Wittgenstein-Symposium in Kirchberg, 2007 - Pichler, Alois (Publications of the Austrian Ludwig Wittgenstein Society - New Series (N.S.), 2008)
This is the second of two volumes of the proceedings from the 30th International Wittgenstein Symposium in Kirchberg, August 2007. It contains selected contributions on the Philosophy of media, Philosophy of the Internet, on Ethics and the political economy of information society. Also included are papers presented in a workshop on electronic philosophy resources and open source/open access.